2017
DOI: 10.1007/s00784-017-2204-1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution MR imaging for dental impressions: a feasibility study

Abstract: The herein described method can be regarded as proof of principle that MRI is a promising option for digital impressions when fixed partial dentures are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Tymofiyeva et al (2008) reported an average deviation between dMRI surfaces and impressions of 0.073 and 0.095 mm for two teeth which had been prepared for inlay placement, and of 0.098 and 0.093 mm for two teeth which had been prepared for crowns. Furthermore, Boldt et al (2017) reported an acceptable fit for one fixed dental F I G U R E 4 Sample results for one patient. The tooth surface reconstruction accuracy of CBCT and dMRI was assessed after alignment with stone cast scans (reference).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Tymofiyeva et al (2008) reported an average deviation between dMRI surfaces and impressions of 0.073 and 0.095 mm for two teeth which had been prepared for inlay placement, and of 0.098 and 0.093 mm for two teeth which had been prepared for crowns. Furthermore, Boldt et al (2017) reported an acceptable fit for one fixed dental F I G U R E 4 Sample results for one patient. The tooth surface reconstruction accuracy of CBCT and dMRI was assessed after alignment with stone cast scans (reference).…”
Section: Discussionmentioning
confidence: 94%
“…Tymofiyeva et al () reported an average deviation between dMRI surfaces and impressions of 0.073 and 0.095 mm for two teeth which had been prepared for inlay placement, and of 0.098 and 0.093 mm for two teeth which had been prepared for crowns. Furthermore, Boldt et al () reported an acceptable fit for one fixed dental prosthesis designed by means of a dMRI‐based impression, but did not quantify the geometric accuracy of tooth surface reconstruction. Both studies used an intraoral coil which can produce high‐resolution images (voxel size up to 0.31 × 0.31 × 0.35 mm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The imaging techniques used in dentistry include digital panoramic radiography (orthopantomography), single-tooth radiography, bitewing X-ray, digital volume tomography (DVT), as well as computed tomography (CT) of the head, magnetic resonance imaging of the temporomandibular joints, and recently magnetic resonance imaging (dental MRI) [1][2][3]. Dental imaging comprises approximately 40 % of radiography examinations performed in Germany.…”
Section: Introductionmentioning
confidence: 99%